(untitled) (The Pakistan Development Review, 1989)
What determines individual earnings and its distribution in a population? The question is an important one both from an analytical as well as a public policy viewpoint. The possible answers to it have a strong bearing on issues of economic efficiency and social equity. Though social scientists have investigated the nature of -income distribution and related matters for a long time, the fascination with the subject along with the list of unresolved questions has persisted. Research regarding the determinants of earnings (or income) has enjoyed a long and venerable tradition in Economics. One such important influence has been the so-called ’human capital school’. The pioneering works of Schultz (1961); Becker (1964) and the follow up study by Mincer (1974) laid the foundations of the theory that investments in human capital such as schooling and on-the-job training enhance productivity which, in turn, leads to higher labour earnings. The basic idea of the human capital school can be expressed in terms of the following semi-log earnings function.